Liquid mind IV unity - Chuck Wild (Hollywood, Calif. : Chuck Wild Records, 2001)
Liquid Mind V: Serenity is, for most listeners, a peaceful and soothing musical journey, designed to help you relax deeply during meditation, massage, yoga, rest, or in times of stress. For many, it is a wonderful background for massage, meditation, healing, yoga, Pilates, Reiki, shiatsu, t'ai chi or reflexology. The tranquil flow of the music, and the absence of regular rhythm, allows some listeners to experience a level of relaxation that may not be achievable with more active music. The fifth in Liquid Mind's elegant electronic series of slow relaxation music albums may take the listener to a place of deep calm and tranquility. This gentle album has been used by some people to relieve stress, by parents to help quiet hyperactive children, by some insomniacs to assist themselves in going back to sleep in the middle of a difficult night, and by others to relieve tension after a busy day at work.
Keywords: Anxiety Disorders -- therapy; Music therapy